PEMANFAATAN INTERNET SEBAGAI SUMBER BELAJAR - Setiyani, Rediana (Dinamika Pendidikan, 2010)
This study has objectives to know (1) the ways / patterns of Internet usage by accounting students of Economics Faculty, Unnes in the academic year of 2009/2010, (2) the benefits of Internet to support the studying of accounting students of Economics Faculty, Unnes in the academic year of 2009/2010 (3) the difference of internet usage as a learning resource among accounting students in 4th semester, 1st and 3rd semester of Economics Faculty at Unnes III in the academic year of 2009/2010. The populations of the study are all accounting program students of Economics Faculty, Unnes. The sampling technique used was stratified random sampling. Method of data collection was questionnaire. Technique of data analysis was descriptive analysis and One Way ANOVA test. The results of this study showed that students who used wifi / hotspot for internet were 57%, students who used the internet cafe were 29.7%, and 13.3% students via modem. Benefit of Internet in supporting their studying was in good categorization, it means that students were sure when they got more information; it would improve their achievement also. There are differences in Internet usage as a learning source by students in II semester and IV semester, students in II semester andÂ  VI semester, students in IV semester and VI semester, students in IV semesterÂ  and VIII semester, students in VI semester and VIII semester. On the other hand, students in II semester and VIII semester were not different. From the results above, the suggestions are: 1) the hotspot area should be increased on the campus; so students can easily access anywhere, 2) the speed of internet access is also added, so students can quickly download information related to their studying, 3) students can take the advantages of hotspot areas in the campus as much as possible so they can get more information and 4) Students should not rely on textbooks only, but also should look for other information that supports their studying.